Avian colibacillosis – current aspects - A. O. Gerasimova; O. B. Novikova; A. A. Savicheva (Ветеринария сегодня)
Colibacillosis is a bacterial disease of humans, animals and birds caused by Escherichia coli, pathogenic gram-negative bacillus. Despite its secondary nature, colibacillosis widely aﬀects poultry farms and causes signiﬁcant economic losses. The disease spread is closely associated with antibiotic resistance problem because a diseased carrier bird may be a reservoir of antibiotic-resistant Escherichia coli strains. In addition, genes of virulence and resistance have been proven to be transferred from avian Escherichia strains toextra intestinal pathogenic strains that are dangerous to humans. Colibacillosis is transmitted aerogenically, alimentally, rarely transovarially, with droppings, mucus, feed, water, handling tools and operating personnel. Birds are most susceptible attheage of1–14days and at the onset of laying period. The disease may present asacute, subacute and chronic forms and is most often manifested by catarrhal hemorrhagic enteritis with profuse foamy diarrhea, respiratory tract lesions, ﬁbrinous peritonitis and polyserositis, as well as a signiﬁcant decrease in weight gains, stunting, egg laying decrease or complete cessation. Colibacillosis is diagnosed comprehensively taking into account the epizootic situation, ﬁndings of clinical examination and postmortem examination of dead or emergency-slaughtered poultry as well as laboratory test and bioassay results. Bacteriological, serological and molecular genetic methods are used for the disease diagnosis. Colibacillosis prevention includes improvement of poultry keeping practice (control of feed and water quality, disinfection, pest control, microclimate control) as well as timely complex vaccination of all poultry. The disease shall be treated taking into account primary etiological factors and bacteria sensitivity to antimicrobials.